2022
DOI: 10.1007/s10851-022-01092-0
|View full text |Cite
|
Sign up to set email alerts
|

Irregularity Index for Vector-Valued Morphological Operators

Abstract: Mathematical morphology is a valuable theory of nonlinear operators widely used for image processing and analysis. Although initially conceived for binary images, mathematical morphology has been successfully extended to vector-valued images using several approaches. Vector-valued morphological operators based on total orders are particularly promising because they circumvent the problem of false colors. On the downside, they often introduce irregularities in the output image. This paper proposes measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The review found anomalies in the topologies of the various variations of bridge graphs or networks, i.e., Gr (Ps, v), Gr (Cs, v) and Gr (Ks, v), honeycomb network HCn, hexagonal network H(m, n), Sierpinski networks, i.e., Sn, S(n, k) networks. Figures 2,4,6,8,10,12,and 14 give the graphical representation of the ISO index for the above-mentioned graphs of networks. Irregularity Sombor Index found lower bounds, upper bounds, and irregularities of all mentioned networks well prediction quality of best characteristic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The review found anomalies in the topologies of the various variations of bridge graphs or networks, i.e., Gr (Ps, v), Gr (Cs, v) and Gr (Ks, v), honeycomb network HCn, hexagonal network H(m, n), Sierpinski networks, i.e., Sn, S(n, k) networks. Figures 2,4,6,8,10,12,and 14 give the graphical representation of the ISO index for the above-mentioned graphs of networks. Irregularity Sombor Index found lower bounds, upper bounds, and irregularities of all mentioned networks well prediction quality of best characteristic.…”
Section: Discussionmentioning
confidence: 99%
“…The nearby irregularity index, which can be taken care of significantly more rapidly by amounting to expected gains of neighborhood windows, yields a lower bound for the general irregularity index. Computational primers with customary pictures outline the possibility of the proposed irregularity indexes [12].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The irregularity introduced by a morphological operator can be measured using the so-called irregularity index [9]. Briefly, the irregularity index is given by the gap between the generalized sum of pixel-wise distance and the Wasserstein metric.…”
Section: Mathematical Morphology and The Irregularity Issuementioning
confidence: 99%
“…Because morphological operators only take into account the partial order ≤, they can introduce irregularities if the image I have pixel values x, y, z ∈ V such that x ≤ y ≤ z but d(x, z) ≤ d(x, y). Accordingly, despite x is closer to z than to y, the inequalities x ≤ y ≤ z suggest w is farther from x than y [9]. Because morphological operators are defined using extrema operators, they do not consider the metric of V, resulting in the irregularity issue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation